Cloning, expression in Escherichia coli, and reconstitution of human myoglobin. - Raghavan Varadarajan; Attila Szabó; Steven G. Boxer (1985)
A full-length cDNA clone for human myoglobin has been isolated from a human skeletal muscle cDNA library. The clone as isolated has a cDNA insert approximately one kilobase long and has 5' and 3' untranslated regions of approximately 80 and 530 base pairs, respectively. The sequence of the translated region corresponds exactly to that predicted for human myoglobin. The cDNA was expressed in high yield in Escherichia coli as a fusion protein consisting of the first 31 amino acids of the phage lambda cII gene, the tetrapeptide Ile-Glu-Gly-Arg, and the myoglobin sequence by following the approach of Nagai and Thogersen [Nagai, K. & Thogersen, M. C. (1984) Nature (London) 309, 810-812]. The fusion product was isolated, reconstituted with heme, cleaved with trypsin, and purified to generate a protein whose properties are indistinguishable from those for authentic human myoglobin. Myoglobin can be readily prepared on a gram scale by using these methods.